NEEDS ANALYSIS OF THE DEVELOPMENT STUDENT WORKSHEET BASED BLENDED LEARNING TO ENCOURAGE MATHEMATICAL LITERACY - Risa Utaminingsih; Cholis Sa’dijah; Abd. Qohar (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Mathematical literacy is the ability of students to carry out activities formulate, apply, and interpret & evaluate mathematics in various contexts. This study aims to analyze the needs of student worksheet development which can stimulate students' mathematical literacy. This type of research is a qualitative descriptive study involving 15 students of class XI MIPA and 2 mathematics teachers of SMA Negeri 1 Gresik. This needs analysis includes material analysis, curriculum analysis, and student analysis. The results showed that one of the difficult mathematics materials for class XI MIPA was linear program, mathematics learning was carried out according to the 2013 Curriculum with the application of Blended Learning in the new normal era, and students still had difficulty solving problems on indicators of interpreting & evaluating mathematical process abilities. Therefore, Student Worksheet based Blended Learning will be developed which is more focused on activities that prioritize the interpretation and analysis of problem solving results according to the limitations and context of the problem in the Linear Program material.